Non-English Major Students Perspectives Towards Teaching and Learning English for Hotels at the Faculty of Economics and Tourism, Souphanouvong University - MANIVONG, Phim; MIXAYKONE , Khanthaly; PHUANGSAVATH, Vatthana; BOUNTHAVONG, Oudalon; THOUMMAVONG, Toulaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
In this research project, the researchers aimed to find out the Non-English Major Students’ Perspectives towards Teaching and Learning English for Hotels at the Faculty of Economics and Tourism, Souphanouvong University. The research consisted of five chapters (1-5). The instrument used for this study was a questionnaire and included 58 items to collect information to find the Students’ Perspectives towards Teaching and Learning English for Hotels at the Faculty of Economics and Tourism with the a total of 229 participants who studied in years 2, 3, and 4. The data was analyzed by using the program SPSS for Windows (Version 17) and Microsoft Excel 2019to analyze information for frequency, average into percentage, mean value and standard deviation (S.D)of this research project. The results of this research revealed that mixed methods of questionnaires and active learning-teaching sessions were used to collect quantitative data that addressed at the purpose of the study. The samples were students from both the Tourismand Hotel Departments at the Faculty of Economics and Tourism, Souphanouvong University. The Analysis of the data illustrated that the students at the Faculty of Economics and Tourism had a positive perspective towards five main components: namely, learning-teaching improvement, the perspectives of the students towards learning, the perspectives of the students towards teaching, the perspectives of the students towards curriculum, and the perspectives of the students towards textbook. The researchers found perspectives towards the Teaching and Learning English for Hotel at the Faculty of Economics and Tourism. However, the majority of the respondents claimed that the perspectives towards textbook were lowerthan the four kinds of teaching and learning English for hotels, such as learning-teaching improvement, learning, teaching and curriculum.In addition, the lowest perspective of students’ personal information towards English learning for hotels; had an extra class at other government schools, were at the pre-intermediate level, andhad never studied English by themselves at all. Moreover, the reasons for studying English; lowest percentage was that students would like to use English to study abroad.